ANALISIS ASPEK YURIDIS DAN ASPEK NON YURIDIS TERHADAP TINDAK PIDANA MENJADI PERANTARA DALAM JUAL BELI NARKOTIKA - Hasudungan Sinaga (IBLAM Law Review)
Many cases of narcotics have gone through controversies or controversial court decisions. That is, the application of norms in the contents of the court decision is still debatable. One example is the Bandung District Court Decision on behalf of the defendant Nana als Ujang Fata Bin Ajuk Marjuki (Alm) No. 1159/Pid.Sus/2021/PN Bdg regarding the case of the crime of Narcotics. This type of legal research is normative legal research. The nature of the research in this study is analytical descriptive in nature. The type of data used in this research is library research. The circulation of narcotics in Indonesia when viewed from a juridical aspect is legal, the Narcotics Law only prohibits the use of narcotics without permission by the law in question. Narcotics crime is used as a promising and rapidly developing business arena, where this activity has an impact on mental damage, both physically and psychologically, to drug users, especially the younger generation. Law enforcement against narcotics crimes has been carried out by many law enforcement officers and has received many judge's decisions. In the non-juridical aspect, in making his decision, in addition to considering matters of a juridical nature, judges also make non-juridical considerations, especially in terms of economic, social and political aspects. directly or indirectly, either implicitly or explicitly, the "integrative philosophy of punishment" in the judge's decision is not solely based on, starting from and only considering the juridical aspect (formal legalistic) solely because if this starting point does not reflect the values the value of justice that should be embodied by the criminal justice system. Some of the legal issues analyzed from the decision are the Complete Format of the Decision but the exploration of non-juridical aspects is not explored in depth in the decision and the aggravating and mitigating reasons for the crime are not explored in depth and the Articles of Indictment are appropriate but do not formulate articles 55 of the Criminal Code regarding inclusion. The need for the formulation of an article regarding inclusion in the indictment of charges and decisions is due to broaden the criminal responsibility of other actors and to facilitate proof for other cases related to case number: No. 1159/Pid.Sus/2021/PN Bdg. Because from the position of the case it is still possible that there are other actors on the DPO (People Wanted List).